Awig-Awig Tenganan Pegringsingan Sebagai Perisai Yuridis Otonomi Desa Dalam Perlindungan Otentisitas Warisan Budaya Tak Benda - Ni Nyoman Raka Astrini (Jayapangus Press, 2026)
This study examines the effectiveness of Awig-Awig in the Traditional Village of Tenganan Pegringsingan as an instrument for safeguarding Intangible Cultural Heritage (ICH) amidst globalization and the intensification of tourism, which often lead to commodification and secularization of sacred rituals. The research aims to demonstrate that customary law sovereignty, grounded in the philosophy of Rwabhineda and the collective leadership system of ulu apad, functions as a juridical shield that preserves cultural authenticity while filling gaps in national regulation. The study employs a socio-legal approach, combining normative analysis of Awig-Awig texts with empirical data obtained through participatory observation and in-depth interviews with customary leaders, academics, and local communities. Findings reveal that preventive mechanisms such as the prohibition of exogamy and strict spatial-temporal regulation of rituals effectively safeguard cultural transmission, while repressive mechanisms through skala-niskala customary sanctions and local mythology reinforce community compliance with cultural and ecological preservation norms. The analysis further highlights that customary law possesses stronger moral binding power and faster responsiveness compared to state law, though it carries potential normative conflicts concerning individual rights to marriage and social mobility. The study concludes that Awig-Awig Tenganan represents a dynamic and sovereign community-based model of cultural protection, though its effectiveness cannot be generalized universally. Policy implications suggest the need for selective adaptation of the Awig-Awig model in other communities, integration of cultural conservation values into public policy, and digitization of customary manuscripts to address generational challenges in the global era.